Sewage waste as substrate for value - Ranjan R.; Rai R.; Kumar V.; Dhar P. (My University, 2025)
With tremendous population growth in the last decade, domestic and industrial sludge waste has become a rising problem. Disposal of sewage waste is conventionally is done through agricultural routes; however, sewage waste can induce harmful effects on the soil quality. In recent years, multiple value-added products have been synthesized from sewage waste, which could be a potential waste management strategy. Bioplastics, bioenergy, surfactants, heavy metals, and biochar are some examples of value-added products obtained from sewage wastes. In this chapter, a complete discussion of sewage waste is done with processes used for converting sewage wastes into value-added products. The explanation further extends to value-added products synthesized from sewage wastes in recent years, laws, and policies associated with products fabricated. © 2024 Elsevier Inc. All rights reserved.